Short- and long-term outcomes of swimming and soccer practice on global motor development during childhood - Rocha, H.; Marinho, D. A.; Costa, A. M. (Science & Sports, 2014)
Introduction: Active children often choose after-school sport experiences, among which swimming and soccer are at the top of the list of most popular sports in several countries. Athletic skills are increased but little is known about the effects on global motor development. The purpose of our study was to analyze changes on global motor development after 5, 10 and 30 months of swimming and soccer practice [1-3]. Methods: The study sample consisted of 35 preschool-aged boys (4.9 ± 0.5 years): 13 children had no involvement in organized sports programs; 11 children were swimmers at a beginner level; 11 children were soccer players at a beginner level. The "test of gross motor development 2" [3] was used to assess children's fundamental movement skill competence (locomotion and object control skills) in three distinct phases: after five (T5), 10 (T10) and 30 (T30) months of accumulated sports practice (practising 2 times per week). Results: Our results showed that the soccer participants had a higher (P < 0.05) global motor ratio (at T5, T10 and T30) and standard scores for locomotion and object control (T10 and T30) than the swimming participants and non-participants. Both sport participant groups significantly improved (P < 0.05) their global motor ratio and the standard scores for locomotion and object control between T5 and T10. Between (T10-T30), the standard scores for control of objects significantly improved (P < 0.05) only for the swimming participants. In fact, the global motor ratio and the standard scores for object control significantly decreased (P < 0.05) between T10 and T30 for soccer participants. No significant changes (P > 0.05) were noted between (T5-T10) and (T10-T30) for non-participants. Conclusions: These results suggest that sports practice during childhood seems to prompt motor development. Despite the improved motor skill competence of the soccer participants at (T5-T10) and (T10-T30), the swimmers showed an ongoing motor development particularly in object control skills.